(3YgO GdfHi Udi Gddg Ydjg hSde ddfUGQis - (3QShd Gddg eMeO Hf YHO Gddg Hf YHO GdeWdH (B( (3Udi Gddg Ydjg hSde (B)s; (3eMeO hdj GdOjf GdeUQj GdTHTjQj GdTGaYj GdGTYQj, CHh GdaVds
(3ChdgG (B:s
(3gPG SLd GdYgO GdPi cJHg eMeO Hf YHO Gddg QShd Gddg Udi Gddg Ydjg hSde Edi cGaI GdfUGQi CLeYjf djchf GdMLI ddg Ydi Ndbg hdjdkG hjcf ddfGS MLI s
(3BNQgG (B:s
(3hefGLGJ ehSi Ydjg CaVd GdUdGI hGdSdGe hMSHfG Gddg hfYe Gdhcjd HeUQ s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdOjGfGJ GdCNQis